2014
DOI: 10.1080/10848770.2014.943529
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating the “New Terrorism”: The Case of the Maoist Insurgency in India

Abstract: In this essay,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There is a consistent deployment of exceptional laws designed to protect the fragile sovereignty of the state (such as the Armed Forces Special Powers Act 1990, the Prevention of Terrorism Act 2002 and Sedition Law 124A of the Indian Penal Code). Suspension of civil rights, abrogation of constitutionally guaranteed citizenship rights and impunity for the security forces to indulge in indiscriminate violence against civilians are the dominant features (Chenoy, 2002; Malreddy, 2014; Sundar, 2014).…”
Section: Excessive Militarism and (In)securities: A Conceptual Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a consistent deployment of exceptional laws designed to protect the fragile sovereignty of the state (such as the Armed Forces Special Powers Act 1990, the Prevention of Terrorism Act 2002 and Sedition Law 124A of the Indian Penal Code). Suspension of civil rights, abrogation of constitutionally guaranteed citizenship rights and impunity for the security forces to indulge in indiscriminate violence against civilians are the dominant features (Chenoy, 2002; Malreddy, 2014; Sundar, 2014).…”
Section: Excessive Militarism and (In)securities: A Conceptual Overviewmentioning
confidence: 99%
“…Several studies have demonstrated that the Indian state, much like its colonial predecessor, continues to unleash indiscriminate violence on its ‘disobedient citizenry’ (Malreddy, 2014: 599) through laws, regulations, policies, armed forces and paramilitary units (Kazi, 2014; Malreddy, 2014; Sundar, 2014). State authorities often cite the objectives of preserving territorial integrity and maintaining national security as the justification for these atrocities.…”
Section: ‘Humanizing’ Militarism Against Popular Dissentmentioning
confidence: 99%
See 1 more Smart Citation
“…The state describes the movement as a 'menace' and as 'left-wing extremism' . It engages in the domestic othering of the Naxalite area of influence ('the Red Corridor') as 'unpatriotic', 'undemocratic', a 'diseased zone' (Malreddy, 2014). For the state,…”
Section: The State Response To the Naxalite Movementmentioning
confidence: 99%
“…The state describes the movement as a ‘menace’ and as ‘left-wing extremism ’ . It engages in the domestic othering of the Naxalite area of influence (‘the Red Corridor’) as ‘unpatriotic’, ‘undemocratic’, a ‘diseased zone’ (Malreddy, 2014). For the state, The perversion of Naxalism has to be traced to its very roots in the ideological concepts like class struggle and class violence and a demonology created by them.…”
Section: The State Response To the Naxalite Movementmentioning
confidence: 99%